Jewish communities on the Ohio River : a history - Shevitz, Amy Hill, 1953- (Ohio River Valley series., 2007)
In Jewish Communities on the Ohio River, Amy Hill Shevitz chronicles the settlement and development of small Jewish communities in towns along the river. In these small towns, Jewish citizens created networks of businesses and families that developed into a distinctive, nineteenth-century middle-class culture. As a minority group with a vital role in each community, Ohio Valley Jews fostered American religious pluralism as they constructed a regional identity. Their contributions to the culture and economy of the region countered the anti-Semitic sentiments of the period.